EFFECT OF ANTI-OXIDANT SUPPLEMENTATION ON POST THAW SPERM CHARACTERISTICS, CELLULAR ENZYME LEAKAGE AND LIPID PEROXIDATION IN BULL SEMEN - RAO, M MUTHA; VERMA, PAWAN KUMAR; BHAT, MUZAFER AHMED; PANDEY, A K; RAINA, R (The Indian Journal of Animal Reproduction, 2023)
A study was conducted to assess the influence of na,Jral (Vitamin E) and synthetic (Butylated Hydroxyl Toluene; BHT) anti-oxidants on post-thaw semen characteristics, enzyme release (lactic dehydrogenase. acid phosphatase and cholinesterase) into extra cellular medium and lipid peroxidation following freezing and thawing in crossbred HF bulls. Semen was collected from three crossbred bulls (HFxT) twice a week and a total of 18 collections (six collections per bull) were utilized in this study. After initial evaluation each semen sample was split into three equal fractions and diluted in tris egg yolk extender containing either vitamin E 0.3mg/ml (TEY-E), BHT 2.0mM (TEY-B) or with out any additive (TEY-C) which acted as control. Filling and sealing of individual diluted semen samples in PVA straws, equilibration at 4 °C for 4h, freezing in programmable freezer and plunging of straws into liquid nitrogen were followed as per standard procedure. Thawing of semen was performed at 37°C for 30 seconds. Post-thaw semen characteristics such as progressive motilitv live sperm(%), and acrosomal integrity (%) were significantly higher and sperm abnormalities were significantly lower in samples containing Vit.E and BHT over the control. The leakage of enzymes (IU/L) such as acid phosphatase, cholinesterase and lactic dehydrogenase was significantly lo,wer in TEY-E followed by TEY-B and highest in the TEY-C diluents. The MDA levels (umol/ml) increased significantly in non-antioxidant added samples (0.60 ± 0.05) over Vit.E (0.11 ± 0.01) and BHT (0.19 ± 0.02) containing samples following thawing. The results revealed that supplementation of Vit.E and BHT to tris egg yolk extender improved the post-thaw semen quality in bulls.